Corporate governance and stock market liquidity in India. (18th June 2012) - Prasanna, P. Krishna; Menon, Anish S.
Corporate governance encompasses the processes for board effectiveness and enhanced transparent disclosures. Both these requirements result in improved quality and quantity of information made available to investors, which in turn is expected to result in informed trading, reduced information asymmetry and improved market liquidity. It was empirically observed that corporate governance had a positive impact on stock liquidity; also, better governed companies had higher liquidity. A decade of governance reforms in India had definitely been beneficial for the firms' adhering to good governance practices. Further, this study examined the relationship between the ownership pattern and the stock liquidity, and found that higher promoter holdings reduce stock liquidity. These results support the arguments of Welker (1995) and Chung et al. (2010) regarding ownership dispersion. The results also validate and strengthen the belief that foreign institutional investors and their investments provide liquidity to emerging stock markets like India.